Microbial community and fermentation characteristic of Italian ryegrass silage prepared with corn stover and lactic acid bacteria. (May 2019) - Yan, Yanhong; Li, Xiaomei; Guan, Hao; Huang, Linkai; Ma, Xiao; Peng, Yan; Li, Zhou; Nie, Gang; Zhou, Jiqiong; Yang, Wenyu; Cai, Yimin; Zhang, Xinquan
Highlights: This is the first investigation on microbial community of mixed silage using SMRT. Mixed silage is characterized by high bacterial diversity. Lactobacillus plantarum was the main species affecting silage fermentation. Heterofermentative Lactobacillus species produced acetate in the silage. The SMRT method provides deep insights into the microbial composition of silages. Abstract: The bacterial community determined via PacBio single molecule, real-time sequencing technology (SMRT) and the fermentation characteristics of Italian ryegrass (IR, 82% moisture) silage prepared with corn stover (CS) were investigated. A selected strain of Lactobacillus plantarum (L694) and a commercial inoculant stain of Lactobacillus plantarum (LP) were used as additives. Lactic acid bacteria (LAB) effectively improved silage quality. After fermentation, Lactobacillus plantarum was the dominant species in IR + LP and IR + L694 treatments, which led to higher ( P < 0.05) lactic acid and lower ( P < 0.05) butyric acid production. Lactobacillus plantarum, Lactobacillus hammesii, Lactobacillus brevis, and Lactobacillus coryniformis were abundantly present in IR + CS + LP and IR + CS + L694 treatments, and acetic acid contents of these were higher ( P < 0.05) than those of other silages. This study demonstrated that addition of CS and LAB can change the microbial community and influence the silage fermentation of IR, and PacBio SMRT reveals more specific microbial information.